Path loss and group delay investigation for in-human body to on-human body transmission using dipole and loop antenna - Haque, Md Ismail (IIUC Studies, 2023)
The most critical aspects for a successful transceiver design for wireless body area communication system are path loss and group delay investigation of the human body. In this research, we used a 150 mm length dipole and 40 mm diameter loop antenna to analyze path loss and group delay at 10-60 MHz HBC band for implant communication. An anatomical human body model in the near field constituency was used with FDTD simulations to build the path loss model. For a small dipole antenna, the path loss increases by an exponent of 6.62 with distance, especially along the height direction of the body, and the average group delay is in the order of 1ns. On the other hand, the average group delay is less than 1 ns and the path loss grows by an exponent of 4.65 for a loop antenna. Finally, it is demonstrated that both antennas have good accuracy and have no effect on data speeds below 20 Mbps but the loop antenna has a better overall performance in this investigation. IIUC Studies, Vol.-20, Issue-1, June 2023, pp. 121-140